Für eine ökonomischere Fundierung der Trend-TFP in der Ermittlung des Produktionspotenzials; For a more economics-based foundation of trend-TFP in the estimation of potential output - Christian R. Proa\~no (Wirtschaftsdienst, 2022)
– In the production function-based approach proposed by the European Commission for the estimation of the potential output, trend total factor productivity (TFP) is indirectly estimated on the basis of cyclical factors. Instead, this article proposes a more economics-based foundation of trend-TFP that is based on the arguments of the endogenous growth theory. A simple econometric exercise shows how the application of this approach may lead to a significantly different assessment of the potential output and, by extension, of the economy's output gap. This may have far-reaching consequences for the conduct of monetary and fiscal policy, e. g. in the context of the German debt brake.
Keywords: C10; E60; O40; 330